2013
DOI: 10.1038/onc.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

CD84 is a survival receptor for CLL cells

Abstract: Chronic lymphocytic leukemia (CLL) is a malignancy of mature lymphocytes that is manifest by the progressive accumulation of transformed cells, mostly due to their decreased apoptosis. CD84 belongs to the Signaling Lymphocyte Activating Molecule (SLAM) family of immunoreceptors and has an as yet unknown function in normal B cells and CLL lymphocytes. We show that CD84 is over-expressed in CLL cells. Activation of cell surface CD84 initiates a signaling cascade, which enhances cell survival. Both immunoneutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 73 publications
1
28
1
Order By: Relevance
“…It is a cell-surface protein that forms homophilic dimers by selfassociation (7)(8)(9). Our studies have previously characterized a survival pathway in CLL regulated by CD84 (10). In addition, we recently showed that CD84 serves as an important bridge mediating the interaction between CLL cells and the various cells in their microenvironment in vitro and in vivo (11).…”
Section: Introductionmentioning
confidence: 95%
“…It is a cell-surface protein that forms homophilic dimers by selfassociation (7)(8)(9). Our studies have previously characterized a survival pathway in CLL regulated by CD84 (10). In addition, we recently showed that CD84 serves as an important bridge mediating the interaction between CLL cells and the various cells in their microenvironment in vitro and in vivo (11).…”
Section: Introductionmentioning
confidence: 95%
“…Additional SLAM family members have been implicated in survival of specific B cell populations; SLAMF5 (CD84) induces survival of CLL cells, which upregulate its expression in a CD74/MIF dependent manner (12, 33). SLAMF1 (CD150) regulates apoptosis, proliferation and differentiation and IgG synthesis of B cells (44, 45).…”
Section: Discussionmentioning
confidence: 99%
“…Purified T cells and B cells (5×10 6 ) were subjected to electroporation as previously described (12). The cells were treated with the following siRNAs: SAP, NTB- A, CD74 (ON-TARGET plus SMART pool) and negative control siRNA (ON-TARGET plus non-targeting pool) (Dharmacon).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations